EDITORIAL - Lourenço, S. O. (Revista de Engenharia Térmica, 2009)
The search for energy sources that alleviate the dependency on fossil fuels is one the greatest challenges of humankind. The environmental damages that result of many decades of gas emissions from burning oil, natural gas, and mineral coal are evident, revealed by the high levels of atmospheric CO2 and by the ocean acidification, for instance. Two fundamental routes will help to reduce the dependence on fossil fuels: the development of machines and engines with more efficient consumption of fuel and the production of renewable sources of energy, such as biofuels. Brazil is probably the country with the highest potential to produce biofuels. The Brazilian success in the production of ethanol since the 1970’s is a world landmark. The recent growth of biodiesel production in Brazil from different sources (e.g., soybeans, bovine fat) is encouraging. New matrixes to produce biodiesel have been tested all over the world. Microalgae represent a world hope to generate advanced biofuels, allying a (potential) huge scale and very high productivity. In theory, microalgae can triplicate their biomass in 24 hours, depending on the species. This high growth rate combined to high accumulation of triglycerides allow the estimates that some microalgae could generate dozens of thousands of liters of biodiesel / ha per year. Microalgae do not follow seasonal crop harvest regimes (they can be harvested on daily basis), they make biofixation of CO2, occupy small physical areas, and can be cultivated in salty or brackish waters, avoiding the competition with scarce water resources for human consumption of irrigation. Fertile lands are unnecessary, since the cultivation includes ponds or photobioreactors, which are independent of the soil characteristics. There is no conflict with land use for agriculture, deforestation of pristine biomes is avoided, and there is the possibility to generate valuable co-products in parallel to biofuel production. Despite these stimulating arguments, no company produces biofuel from microalgae at commercial scale. Several hurdles still have to be overcome, such as the cost and the efficiency of the separation of the cells from the liquid medium, the accumulation of more triglycerides by the microalgae, the reduction of costs of the systems for mixing the cultivation and dissolution of CO2, and the scarce availability of water in key regions, among others. All technical problems put together and the high intensity of manpower result in high costs of production of biofuels from microalgae. Probably it is not possible yet to produce 1 liter of microalgae biodiesel for less than US 9.00, a value that makes the incorporation of microalgae to the world matrix of biofuel to be economically impossible, using the current technology. Due to the Brazilian tradition on biofuels, there is a tremendous international expectation on the participation of Brazil in the production of biofuels from microalgae. Several Brazilian groups have been working on the challenge of creating solutions to make feasible the cultivation of microalgae to generate biofuels. In the previous issue of Engenharia Térmica, two good examples of the Brazilian effort to develop microalgae production can be evaluated by the readers. Ribeiro et al. offered a mathematical analysis of the growth of Phaeodactylum tricornutum, a fast-growing marine microalga, in a closed system for cultivation - a photobioreactor. Torrens et al. evaluated the properties of different kinds of biodiesel generated from microalgae and their theoretical gas emissions in engines, based on the characteristics of their fatty acid composition. These initiatives are important and very welcome. Hopefully, these promising results will stimulate the development of the field in the country, attract more researchers to the subject, and inspire the cooperation among multidisciplinary Brazilian teams.